NIAT BELI ULANG GENERASI Z DAN MILLENIAL DALAM MENGGUNAKAN E-COMMERCE: ditinjau dari E-wom, Kepercayaan dan Resiko - Wiwik; Evi Susanti; Zurlina Lubis (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Transactions using e-commerce are a form of changing the buying and selling culture, especially after the Covid 19 Pandemic. This transaction can facilitate and benefit both parties. This study focuses on consumer repurchase intentions from electronic word of mouth (e-Wom, trust, and risk. The research was conducted from February to July 2021 with e-commerce as the research object. A conditional sample was used to ensure that the data obtained was valid and could be accounted for, namely the age group of generation Z and millennials who use e-commerce and are domiciled in DKI Jakarta Province, with a total sample of 120. The results show that generation Z and millennial consumers' repurchase intention is influenced by e-Wom and trust. It is also a consideration for consumers to make repeat transactions. The results of this study also prove that generation Z and millennial consumers prefer to use E-commerce in making purchases. It shows that to attract the attention of this generation, companies can build repeat purchases on e-commerce by maintaining positive e-Wom to create the same trust very high, and the risk of buying online is shallow.